2005
DOI: 10.1007/s00330-005-2881-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a small field-of-view size on the detection of coronary artery calcifications with MSCT: in vitro and in vivo study

Abstract: The purpose of this study is to asses the impact of small field-of-view (FOV) sizes on the detection of coronary artery calcifications using multislice-spiral computed tomography (MSCT). First, a static chest phantom containing calcium inserts was scanned 10 times using a standardized scan protocol. Secondly, 50 patients (28 male, 63.6+/-10.6 years) underwent cardiac MSCT using the same protocol. Images were reconstructed with three different FOV sizes (180x180, 220x220, 380x380 mm(2)). Coronary calcium scorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The cost for performing calcium scoring using EBT was based on the cost for MSCT coronary calcium scoring, since there is no cost difference between those two methods in the reimbursement system. This also has the advantage of reflecting the clinical ability to perform calcium scoring using MSCT [22][23][24]. Diagnostic accuracy of calcium scoring, however, was based on the results obtained with EBT, since far fewer data are available for MSCT in this regard.…”
Section: Methodsmentioning
confidence: 99%
“…The cost for performing calcium scoring using EBT was based on the cost for MSCT coronary calcium scoring, since there is no cost difference between those two methods in the reimbursement system. This also has the advantage of reflecting the clinical ability to perform calcium scoring using MSCT [22][23][24]. Diagnostic accuracy of calcium scoring, however, was based on the results obtained with EBT, since far fewer data are available for MSCT in this regard.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of calcium, expressed as Agatston score, 12 was quantified by a software package (Aquarius iNtuition, TeraRecon, Foster City, US), for each calcified lesion, using the widely utilized threshold of 130 HU in nontriggered and ECG-triggered scan. 13 Thresholds from 90 to 160 HU, with steps of 10 HU, were also used in nontriggered scan to analyze the influence of threshold on the agreement of calcium scores between these two techniques. Calcium scores derived from nontriggered thoracic CT examinations with velocities of 0-90 mm/s were considered as index test results, because these velocities were in the common coronary velocity range in a cardiac cycle.…”
Section: C Quantitative Image Analysismentioning
confidence: 99%
“…Also, we used a larger field of view than traditionally used for CAC evaluation. However, Hong and colleagues [20] and Mahnken and colleagues [21] had found that variations in the field of view had a negligible effect on CAC Score but found that the use of a larger field of view decreased the sensitivity of detecting small CAC.…”
Section: Discussionmentioning
confidence: 97%